Does the outsourcing strategy to offshore UK call centres affect customer satisfaction and loyalty of UK student consumers? - Sandhu, Gurjeven (2007)
The offshoring of call centres to cheaper countries, such as India, is a popular topic of discussion at the moment. This practice raises a number of ethical and organisational considerations. But how is it affecting the customers of these organisations? This research will investigate how student consumers have been affected by the offshoring trend in terms of service quality, customer satisfaction and loyalty. The research questioned people's general experiences of call centres so included; telephone companies, banks, utilities companies, National Rail Enquiries and others.